Remimazolam in children: a comprehensive narrative review - Tom G. Hansen; Thomas Engelhardt (Anesthesiology and Perioperative Science)
Abstract Remimazolam is a novel ultra-short-acting benzodiazepine gaining attention for its rapid onset, predictable pharmacokinetics, and favorable safety profile in adult procedural sedation and anesthesia. Early pediatric data suggest it may offer significant advantages over traditional sedatives, including enhanced predictability, improved safety, and faster recovery times. Despite these promising attributes, its routine use in pediatric populations remains underexplored and unestablished. This narrative review examines remimazolam’s pharmacological properties, including its mechanism of action, metabolism, and elimination, and evaluates its safety and efficacy in pediatric sedation. Potential clinical applications are highlighted, such as procedural sedation, intensive care, and anesthesia induction, with comparisons to conventional agents. While initial studies suggest benefits, critical gaps remain in understanding its use in children. These include age-specific dosing strategies, long-term safety considerations, and its efficacy in children with comorbid conditions or undergoing complex procedures. Addressing these gaps will require robust clinical trials and large-scale observational studies. This review synthesizes current evidence and explores the potential of remimazolam to enhance pediatric sedation and anesthesia practices. By identifying key knowledge gaps and proposing future research directions, it aims to inform clinicians and researchers about the role of remimazolam in improving safety and outcomes in pediatric anesthesia.